Influence of socio-demographic issues in body mass index (BMI) of drug addicts in methadone maintenance treatment - Costa, Ana Filipa (2012)
The purpose of this study was to investigate the influence of social factors on the nutritional status of drug addicts. 60 drug addicts in methadone maintenance treatment of Integrated Response Center (CRI) of Bragança were evaluated. Nutritional assessment was performed by measuring the weight and height and then calculated the body mass index. The socio-demographic data were collected through a questionnaire constructed for this purpose. PASW 19.0 for Windows. The average body mass index (BMI) was 22.46 ± 3.36 kg/m2 and based on this parameter 13.3% were underweight, 65% normal weight, 20.0% overweight and 1,7% obesity grade I. BMI was significantly higher in addicts who live with a spouse in relation to other housing contexts (p <0.005). In terms of marital status, unmarried addicts had a significantly lower BMI compared to other situations. Individuals have an average of 4.10 ± 4.47 years of treatment and 78.3% performed less than 3 meals/day. The socio-demographic conditions must be taken into consideration in the process of intervention with this population. More studies must be performed in other to clarify other food behavior variables in drug users populations.